A critique on the theory of homeostasis - De Luca, Laurival A. [UNESP] (Elsevier, 2022)
The objective of this critique is to demonstrate that the theory of “internal environment” (TIE) does not support the theory of “homeostasis” (TOH). We review and conclude that remains valid the concept of “internal environment”, which corresponds anatomically to the extracellular fluid (ECF) that bathes tissue cells. The Claude Bernard's classification of “life”, a corollary of the TIE under a strict “reactive” paradigm, we then interpret as a classification of how animals behave in response to environmental changes. According to such interpretation, the two theories agree that, when facing changes in the external environment, animals with “free” behavior regulate essential metabolism factors present in the ECF. These are “internalized environmental factors” or IEF (temperature, O2, water, and basic organic and inorganic “nutrients”), a marine legacy of the evolution of the body fluid compartments. However, we show that have empirical and logical shortcomings key inferences derived from the TIE. Such inferences representing traditional premises of TOH we summarize here in two axioms: “if free behavior then regulated IEF” and “all behavioral mechanisms regulate the IEF”. In addition, whereas “stability” means “free behavior versus dormancy” in TIE, it means “tissue cells that resist destruction” in TOH. This leads to inevitable contradictions, here discussed at length, that reduce the scope of TOH. We might be in need of a theory that considers not only where TIE and TOH are superficially valid, but also where they crucially diverge, in order to explain “stability” as applied to physiology and behavior.
Keywords: Behavior; Biological clock; Body-fluid compartment; Internal environment; Regulation; Stability